Analysis of the Youth Policies and Its Impact on the Economic Policy of the State for the Tourism Development - JAKUPOVA, Dinara; KOSHEBAYEVA, Gaukhar; ALPYSBAYEVA, Nazym; BIRYUKOV, Valeriy (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The purpose of the study is to analyze the formation of youth policy in the Republic of Kazakhstan and identify factors influencing its development, including the tourism industry. Youth is one of the socially active segments of the population with important potential weight in the future, which is an independent direction of the state, based on legal, ideological and institutional mechanisms. The desire of the majority of young people to independently resolve their issues and build a life perspective was reflected in her increased craving for education, mastering prestigious professions. The value of education, which has largely lost its significance for young people, has taken its place among the priority life values of young people.  The findings of our analysis conducted in this research paper highlighted that also the tourism industry, as part of the economic system, is certainly no exception and is not immune to these needs; the impact of policies for the development of youth should generate a growing competition both for the talented managers and teachers, students, young people which could be involved in the development of the tourism industry.